TRANSPARENCY VILLAGE REVENUE AND EXPENDITURE BUDGET 2024 THROUGH DIGITAL INFORMATION DISCLOSURE IN JETIS VILLAGE GUNUNGKIDUL REGENCY - Inggrit Devi Saputri; Gerry Katon Mahendra (DIA: Jurnal Administrasi Publik, 2026)
Transparency in the management of the Village Revenue and Expenditure Budget (APBKal) is one of the principles for realizing good village governance. The development of digitalization can be an opportunity to utilize websites as a means of budget information disclosure. This study aims to describe the implementation of digital-based transparency in the management of APBKal in Jetis Village and identify the factors that influence it. Qualitative methods were used in this study with data collection techniques, observation, interviews, and documentation as well as data analysis using the interactive model of Miles and Huberman. The analytical framework used was the management theory of Terry and Rue and the transparency theory of Kristianten. The results of the study indicate that the APBKal management mechanism in Jetis Village has been carried out procedurally and participatory, but digital-based transparency is still not optimally implemented. The obstacles faced include limited infrastructure, low capacity and discipline of officials in updating information, low digital literacy of the community, and accessibility of the website portal that is not yet user-friendly. These findings emphasize the need to increase the capacity of the apparatus and strengthen regulations, simplify website portals and information formats, and increase outreach to optimize digital transparency in the management of the Village Revenue And Expenditure Budget (APBKal)